2021
DOI: 10.1016/j.ijwd.2021.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical considerations in the management of hidradenitis suppurativa in women

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory disease of the skin with a predilection for women. The role of sex hormones, including estrogen and progesterone, is incompletely understood, but alterations in hormone levels may play a role in disease activity for many patients. Specific clinical considerations should be made for women with HS, particularly in the setting of pregnancy, childbirth, breastfeeding, and menopause. Current knowledge gaps regarding HS include the cumulative impact of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
14
0
3
Order By: Relevance
“…Levels of sex hormones are influenced by age, the menstrual cycle, pregnancy and medication such as the contraceptive pill 29,30 . Whilst the influence of sex hormones on the activity of HS is well documented 10 , the link between sex hormones and inflammatory cytokines and chemokines in HS is not well understood. Monocyte populations are known to be altered in the setting of HS 19,26,27 with trends toward non-classical populations observed 19,26 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Levels of sex hormones are influenced by age, the menstrual cycle, pregnancy and medication such as the contraceptive pill 29,30 . Whilst the influence of sex hormones on the activity of HS is well documented 10 , the link between sex hormones and inflammatory cytokines and chemokines in HS is not well understood. Monocyte populations are known to be altered in the setting of HS 19,26,27 with trends toward non-classical populations observed 19,26 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The immense psychosocial impact of HS, a disease that is long-lasting and involves pain, malodour and dis guring scars, has been very well documented. 25 Stigmatization is customary among HS patients and is more frequent and severe than that experienced as a result of other skin diseases. 26 It is not only the result of the disease's symptoms, but of people's ignorance regarding HS as well.…”
Section: Discussionmentioning
confidence: 99%
“…There are clear associations with hidradenitis suppurativa (HS) and conditions associated with androgen excess, including acne vulgaris, hirsutism, and irregular menses 19–21 . Flaring of HS with the menstrual cycle is reported to occur in as many as 63% of affected women 22 . The impact of menopause on HS activity is unclear, with some studies reporting an improvement with menopause in 48% of women 20 .…”
Section: Common Dermatoses After Menopausementioning
confidence: 99%
“…A study found no significant difference in androgen receptor and ER activity in apocrine glands in patients with HS 24 . Despite this, there does appear to be a benefit with antiandrogenic therapy 22,25 . There is anecdotal evidence that HRT can cause deterioration in HS symptoms 22 .…”
Section: Common Dermatoses After Menopausementioning
confidence: 99%
See 1 more Smart Citation